Traditional and new raw materials for spirit beverage production - Ługowoj, Szymon; Balcerek, Maria (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2021)
The ethanol production industry is a fast growing branch of the economy in many countries, and there is a rich tradition of spirit beverage production of many unique drinks such as Polish vodka and Starka or Irish and Scotch whisk(e)y, all of which have unique organoleptic features. This variety is possible thanks to different raw materials used for production such as rye, barley or corn and potatoes, as well as technological solutions developed over the generations of manufacturing. Rye deserves a closer look due to its low growth requirements and many different uses as well as its long tradition of cultivation, especially in Poland. On the other hand, manufacturers are currently interested in using new, original raw materials for the production of so-called craft alcohols. Buckwheat is an example of a raw material that can be successfully used in the production of original spirits.